Implementation of innovative aeronautical communication, navigation and surveillance (CNS) systems - Stojce Ilcev, Dimov (International Journal of Engineering and Technology, 2019)
This paper introduces implementation of innovative Satellite Communication, Navigation and Surveillance (CNS) systems in function of Global Satellite Augmentation System (GSAS) integrated by the current and new projected Regional Satellite Augmentation System (RSAS) worldwide. The satellite communication and navigation systems are presently in use, however the main aspect of any hypothetical RSAS network is implementation of satellite surveillance system employing previous and new CNS solutions for improved Air Traffic Control (ATC) and Air Traffic Management (ATM) in all phases of flight, approaching to airports and during landing. The CNS network also enhances safety and emergency systems, transport security and control of transportation freight, logistics and the security of the crew and passengers onboard aircraft. The proposals for modern multifunctional space segment, DVB-RCS network, RSAS infrastructure, Satellite Automatic Dependent Surveillance-Broadcast SADS-B system for surveillance and movement guidance and control are also discussed as special solutions in airports environments.Â Â Â